Evaluation of clinicopathological parameters and immunoexpression of heat shock protein -27 in breast carcinoma and metastatic lymph nodes - Saroha N; Adil SAK (Journal of Medical and Scientific Research, 2025)
Background: Breast cancer, the second most common worldwide, causes significant morbidity and mortality in developing nations. Aberrant HSP-27 expression links to aggressive tumors, chemotherapy resistance, and poor prognosis. The stage of disease at diagnosis is the most important prognostic variable. Hence, this study was undertaken to evaluate the expression of HSP-27 in Invasive breast carcinoma and metastatic regional lymph nodes.